Discovery, Bioactivity Evaluation, Biosynthetic Gene Cluster Identification, and Heterologous Expression of Novel Albofungin Derivatives - She, Weiyi; Ye, Wenkang; Cheng, Aifang; Liu, Xin; Tang, Jianwei; Lan, Yi; Chen, Feng; Qian, Pei-Yuan (Frontiers in Microbiology, 2021)
The crude extract of Streptomyces chrestomyceticus exhibited strong and broad activities against most “ESKAPE pathogens”. We conducted a comprehensive chemical investigation for secondary metabolites from the S. chrestomyceticus strain and identified two novel albofungin derivatives, i.e., albofungins A (1) and B (2), along with two known compounds, i.e., albofungin (3) and chloroalbofungin (4). The chemical structures of the novel compounds were elucidated using HRMS, 1D and 2D NMR, and electronic circular dichroism spectroscopy. The draft genome of S. chrestomyceticus was sequenced, and a 72 kb albofungin (alb) gene cluster with 72 open reading frames encoding type II polyketide synthases, regulators and transporters, and tailoring enzymes was identified using bioinformatics analysis. The alb gene cluster was confirmed using the heterologous expression in Streptomyces coelicolor, which successfully produced the compounds 3 and 4. Furthermore, compounds 1 to 4 displayed remarkable activities against Gram-positive bacteria and antitumor activities towards various cancer cells. Notably, compounds 1 and 3 showed potent activities against Gram-negative pathogenic bacteria. The terminal deoxynucleotidyl transferase (dUTP) nick-end labeling and flow cytometry analyses verified that compound 1 inhibited cancer cell proliferation by inducing cellular apoptosis. These results indicated that albofungins might be potential candidates for the development of antibiotics and antitumor drugs.